2020
DOI: 10.1101/2020.10.16.342311
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping sites of carboxymethyllysine modification on proteins reveals its consequences for proteostasis and cell proliferation

Abstract: Posttranslational mechanisms play a key role in modifying the abundance and function of cellular proteins. Among these, modification by advanced glycation end products (AGEs) has been shown to accumulate during aging and age-associated diseases but specific protein targets and functional consequences remain largely unexplored. Here, we devised a proteomic strategy to identify specific sites of carboxymethyllysine (CML) modification, one of the most abundant AGEs. We identified over 1000 sites of CML modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 114 publications
1
3
0
Order By: Relevance
“…While only a few proteins (∼20 out of ∼4,400 identified proteins) were altered significantly by proteome analysis (Yu et al, 2020), ∼480 out of ∼1,670 identified proteins pulled-down with Con A were significantly regulated and ∼80 out of ∼900 proteins pulleddown with PNA. This confirms previous data that enrichment strategies help to detect ageing-related alterations (Di Sanzo et al, 2020). In agreement with the whole proteome analysis (Yu et al, 2020), our analysis also identified electron transport and inflammation to be regulated during aging.…”
Section: Discussionsupporting
confidence: 91%
“…While only a few proteins (∼20 out of ∼4,400 identified proteins) were altered significantly by proteome analysis (Yu et al, 2020), ∼480 out of ∼1,670 identified proteins pulled-down with Con A were significantly regulated and ∼80 out of ∼900 proteins pulleddown with PNA. This confirms previous data that enrichment strategies help to detect ageing-related alterations (Di Sanzo et al, 2020). In agreement with the whole proteome analysis (Yu et al, 2020), our analysis also identified electron transport and inflammation to be regulated during aging.…”
Section: Discussionsupporting
confidence: 91%
“…Proteome data for liver were obtained from Di Sanzo et al 43 Proteome data for brain, spleen and lung were taken from Yu et al, 44 and used to prepare Figure S2A comparing immune cell marker levels between young (4 months) and old mice (18 months). For detailed information about sample processing and measurement please refer to Yu et al 44 …”
Section: Methodsmentioning
confidence: 99%
“…Labelling efficiency was checked, followed by sample pooling (5‐10 µg of each sample), peptide desalting with Oasis HLB µElution plate (Waters) and subjected to high pH fractionation prior to LC‐MS/MS analysis on an Orbitrap Fusion Lumos tribrid mass spectrometer (Thermo Fisher Scientific). Data were searched with Mascot v2.5.1 (Matrix Science) using Proteome Discoverer v.2.0 (Thermo Fisher Scientific) and further processed with in‐house written scripts using R v3.6.3 in R Studio Server v1.2.5042, as described previously 43 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation